2022
DOI: 10.1101/2022.08.31.505555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Norepinephrine regulates Ca2+ signals and fate of oligodendrocyte progenitor cells in the cortex

Abstract: Oligodendrocyte precursor cells (OPCs) represent the most abundant group of proliferating cells in the adult central nervous system. OPCs serve as progenitors for oligodendrocyte (OLs) throughout the life, and contribute to developmental and adaptive myelination, and myelin repair during diseased state. OPCs make synaptic and extra-synaptic contacts with axons, and detect and respond to neuronal activity. How OPCs translate the information relayed by the neuronal activity into Ca2+ signals, which in turn influ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…We found that 99% of Ca 2+ events in OPCs occurred in MDs on processes, and 97% of OPCs exhibited only MD Ca 2+ activity during our recordings (Fig. 6c, Supplemental Video 3-4), consistent with recent work in mammals 43,44 . We examined the proximity between Ca 2+ events in MDs and a presynaptic marker, synaptophysin-RFP 17 .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We found that 99% of Ca 2+ events in OPCs occurred in MDs on processes, and 97% of OPCs exhibited only MD Ca 2+ activity during our recordings (Fig. 6c, Supplemental Video 3-4), consistent with recent work in mammals 43,44 . We examined the proximity between Ca 2+ events in MDs and a presynaptic marker, synaptophysin-RFP 17 .…”
Section: Resultssupporting
confidence: 91%
“…For example, some OPCs exhibit no change or even an increase of Ca 2+ activity upon TeNT treatment or TTX treatment while most OPCs exhibit reduction. These “outlier” OPCs and activity could be due to Ca 2+ generated from synapse-independent mechanisms, such as adrenergic receptor-mediated Ca 2+ activity as recently suggested in cerebral cortex 43,44 . In line with this, nearly 61% of Ca 2+ MDs do not associate with presynaptic markers, and nearly 55% residual Ca 2+ activity remains after TeNT treatment, supporting synapse-independent Ca 2+ - inducing mechanisms in OPCs as well as synapse-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, arousal-dependent changes in mitochondria motility is consistent with recent evidence of decreased calcium dynamics in OPCs in anesthesia conditions or when norepinephrine release is blocked 63 . Norepinephrine can influence the differentiation and/or proliferation of oligodendrocytes and the expression of norepinephrine receptors in the OPCs changes with their differentiation 63,64,67 . Overall, these observations suggest a potential connection between mitochondria and calcium dynamics and raise questions for how animal arousal state influences mitochondria in these cells and therefore the cell fate in the oligodendrocyte lineage.…”
Section: Discussionmentioning
confidence: 99%